Medical waste management in Al-Kut City (Journal of Engineering, 2013)
This research investigates solid waste management in Al-Kut City. It included the collection of medical and general solid waste generated in five hospitals different in their specialization and capacity through one week, starting from 03/02/2012. Samples were  collected and analyzed periodically to find their generation rate, composition, and physical properties. Analysis results indicated that generation rate ranged between (1102 – 212) kg / bed / day, moisture content and density were (19.0 % - 197 kg/ m3) respectively for medical waste and (41%-255 kg/ m3) respectively for general waste. Theoretically, medical solid waste generated in Al-Kut City (like any other city), affected by capacity, number of patients in a day, and hospital specialty The research exposed the incorrect ways used in collecting, storing, waste transport, and inefficient incinerators processing .Laboratory test for six ash collected samples indicated high concentration of heavy metals (Pb, Cd, Cr) , having the rang of (51.0 – 62.0) mg / l of lead, (3.0 – 8.5) mg / l for cadmium, and (43.0 -69.0) mg / l for chrome. In comparison with the US Environmental Protection Agency standards, these samples are higher than the recommended levels that may threat groundwater. A comprehensive and integrated solution there must be to manage medical waste, with the participation of all parties concerned, especially, the Ministry of Health, environment authorities concerned, and the participation of civil society organizations. A color-code trash bags and containers are recommended by the World Health Organization and the Environmental Protection Agency to be used in hospitals that propose red bags for collecting medical waste while black bags for general waste provided that they are resistant to tearing seeping and should be provided in sufficient numbers.